2019
DOI: 10.3390/polym11010090
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Compactability and Cracking Behavior of Polyacrylamide-Treated Saline Soil in Gansu Province, China

Abstract: Polyacrylamide (PAM) is a water-soluble polymer with the ability to enhance a soil’s stability. PAM is currently being used to prevent irrigation-induced erosion and enhance the infiltration in farmland soil. To improve the compaction properties of the saline-soil-based filling material that is used in highway subgrade and the cracking resistance capacity of a saline soil’s crust, the consistency limits, compactability, microstructure, and cracking morphology of untreated and PAM-treated saline soil were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Under a 0.04% PAM dosage, the time required to achieve the same infiltration depth was the longest. This is because PAM is a long-chain polymer compound that primarily impacts the viscosity of soil water [34,35]. With the increase in PAM dosage, the ability of PAM to bond to soil water improved, and the viscosity of soil water increased, resulting in a decrease in the soil water infiltration rate [11].…”
Section: Effect Of Pam Dosages On Infiltration Characteristics Of Bra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under a 0.04% PAM dosage, the time required to achieve the same infiltration depth was the longest. This is because PAM is a long-chain polymer compound that primarily impacts the viscosity of soil water [34,35]. With the increase in PAM dosage, the ability of PAM to bond to soil water improved, and the viscosity of soil water increased, resulting in a decrease in the soil water infiltration rate [11].…”
Section: Effect Of Pam Dosages On Infiltration Characteristics Of Bra...mentioning
confidence: 99%
“…When the PAM dosage was 0.04%, the sorption rate S dropped to 0.547 cm/min 0.5 , showing that the capillary force's ability to absorb water in soil was decreased. The reason for this could be that the hydrogel generated when PAM was introduced to the soil increased the viscosity of water, decreasing the capillary force's water absorption capacity [11,34]. The capillary force's water absorption capacity in soil was lowest when the PAM application rate was 0.04%.…”
Section: Effect Of Pam Dosages On Infiltration Model Parametersmentioning
confidence: 99%
“…This not only prevents external moisture from infiltrating but also reduces the rate of water evaporation; When the moisture between soil particles decreases significantly, soil particles absorb moisture from the interior of the AP through surface tension to replenish the moisture between soil particles. Therefore, AP can regulate the change of soil water content, reduce the evaporation rate of water in porous media 43 , 44 , the drying shrinkage effect is weakened (the surface tension between soil particles), and the crack resistance is improved. As shown in Fig.…”
Section: Discussion and Analysis Of Improved Mechanismsmentioning
confidence: 99%
“…The wet–dry cycle test results show that the wet–dry cycle resistance of geosynthetic clay liners can be significantly improved by partially replacing bentonite with a super absorbent polymer. In addition, Zhang et al [ 14 ] showed that with the increase in the PAM content, the intersection point and crack length of the compacted saline soil crack network decreased. These results indicate that the increase in PAM reduces the shrinkage strain and defects or pores of saline soil.…”
Section: Introductionmentioning
confidence: 99%